Outcomes associated with asthma or wheezing illness in the fifth year of life - Waters, A-M; Ampon, R; Marks, G; Reddel, H; Zinoviev, A; Poulos, L; Xuan, W (My University, 2009)
Background: Children with asthma experience poorer health outcomes compared with other children. Objective: We quantified the impact on kindergarten-age children of reported wheeze or ever–diagnosed asthma on health outcomes over the ensuing two years. Methods: Children from a population cohort were classified as having or not having reported wheeze or ever–diagnosed asthma at baseline (4–5 years). Two–year follow-up data were used to examine caregiver-reported health outcomes. Rate ratios and population attributable fractions were estimated. Results: The prevalence of reported wheeze or ever–diagnosed asthma at age 4–5 years was 28%. The presence of either of these problems doubled the risk of hospitalisation (RR 2.04, 95% CI 1.48–2.79), frequent general practice visits (RR 2.07 (1.71–2.51)) and reporting fair/poor health status (RR 2.19 (1.35–3.56)) over the next two years. The population attributable fractions of wheeze or ever–diagnosed asthma for these outcomes at age 6–7 years were 22.3%, 22.8% and 24.9%, respectively. Moderate associations were also found between wheeze or ever–diagnosed asthma and school absenteeism of two or more days, emergency department visits and excess weight. There was no evidence of any impact of asthma at baseline on height attained at age 6–7 years. Conclusions: Poorer health outcomes at age 6–7 years can be predicted from the presence of asthma or asthma symptoms at age 4–5 years. Acknowledgements: ACAM is an Australian Institute of Health and Welfare collaborating unit, funded by the Department of Health and Ageing.
Keywords: Children; Health -- Medical conditions; Health and wellbeing; Children; Health; Medical conditions; Health and wellbeing